A new approach for energy efficiency in MANET based on the OLSR protocol. (1st January 2012) - Hamrioui, Sofiane; Lalam, Mustapha; Lorenz, Pascal
One of the critical issues in Mobile Ad hoc Network (MANET) is the energy efficiency. The challenge is how to extend the limited lifetime of energy in mobile nodes. We proposed a new approach to minimise the energy consumption called EM-OLSR (Energy Efficiency in MANET by improving OLSR protocol). EM-OLSR is based on the OLSR routing protocol and adds a new energy fairness parameter to the Multi-Point Relay (MPR) technique. This new parameter is used by our approach and allows fairness energy consumption in the same set of MPR. In this mechanism, nodes with low power are prevented in the routing process in order to maintain similar power values for all the mobile nodes. The simulation results showed that our proposed EM-OLSR approach allow significant power saving up to 14% and an increase in average lifetime of a mobile node as high as 22%.